TECHNOLOGY OF FREEZE-DRYING OF RAW MEAT - Ergashev , Oybek; Meliboyev, Mirazam; Qurbonov , Ulug’bek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: Expanding the assortment of agricultural products and providing the population with ecologically clean, natural and safe food products is one of the urgent issues today. Currently, many agricultural products, mainly finished and semi-finished products made from meat products, as well as problems of long-term storage of meat raw materials, or problems such as low structural quality indicators in production productsit is considered one of the priority issues. as a solution to these problems, there is a possibility to apply sublimation drying technology, which is now popular, as a solution. In short, the types of products produced, as well as long-term storage of meat raw materials through drying, are important as they can ensure high efficiency in termsof composition. Drying products makes it possible to provide the population with agricultural products throughout the year. In addition, the demand for dried ecologically clean products is very highly valued in the world market.